Huge crowd for Tiwi Grand Final
tag=1 data=Huge crowd for Tiwi Grand Final tag=3 data=NT News tag=8 data=SPORT tag=9 data=BATHURST ISLAND% TIWI ISLANDS%TIWI GRAND FINAL tag=32 data=WOODRIDGE, MICHAEL%COSTELLO, PETER%PURUNTATAMERI, BARRY%BURKE, DENIS tag=34 data=PRSS tag=61 data=09 tag=62 data=Apr tag=63 data=2001